Assessing the Socio-Economic Benefits of Urban Road Improvements in Developing Cities - Mohamad, Dadang (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
This study evaluates the socio-economic benefits of urban road improvements in developing cities. It aims to assess how road enhancements impact economic development and social well-being. Using a mixed-methods approach, the research includes qualitative interviews with local residents and stakeholders, as well as quantitative analysis of economic indicators and social metrics. The findings demonstrate significant improvements in economic activities, increased property values, and enhanced quality of life. The study provides insights for policymakers and urban planners to optimize infrastructure investments for maximizing socio-economic benefits in urban areas.